2018
DOI: 10.1002/14651858.cd006089.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for acute rhinosinusitis in adults

Abstract: Background Acute rhinosinusitis is an acute infection of the nasal passages and paranasal sinuses that lasts less than four weeks. Diagnosis of acute rhinosinusitis is generally based on clinical signs and symptoms in ambulatory care settings. Technical investigations are not routinely performed, nor are they recommended in most countries. Some trials show a trend in favour of antibiotics, but the balance of benefit versus harm is unclear. We merged two Cochrane Reviews for this update, which comprised di eren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 54 publications
1
41
1
11
Order By: Relevance
“…Trials using imaging (3 radiography, 1 CT) found a larger benefit, suggesting some validity for the concept of imaging as a reference standard. 6 To date no randomized trials of antibiotics or other interventions have enrolled patients with ABRS diagnosed by inspection of fluid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trials using imaging (3 radiography, 1 CT) found a larger benefit, suggesting some validity for the concept of imaging as a reference standard. 6 To date no randomized trials of antibiotics or other interventions have enrolled patients with ABRS diagnosed by inspection of fluid.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review found a 5% absolute increase in the rate of cure with antibiotics for clinically diagnosed ARS, compared with an 11% increase in rate of cure with imaging-diagnosed ARS; more accurate clinical diagnosis could identify the patients most likely to benefit from antibiotics. 6 Previ-ous systematic reviews of the clinical diagnosis of ARS are all more than 15 years old and did not use modern analytic techniques such as bivariate meta-analysis. [7][8][9][10] The goal of the current study is therefore to perform a comprehensive meta-analysis of the clinical diagnosis of ARS and ABRS.…”
Section: Introductionmentioning
confidence: 99%
“…27 Antibiotic treatment is associated with a shorter duration of symptoms (NNT = 19) but an increased risk of adverse events (NNH = 8). 7,19 Amoxicillin with or without clavulanate for 5 to 10 days is first-line antibiotic therapy for most adults with ABRS. 1,3,5,8,9,11 Per AAO-HNS, the "justification for amoxicillin as first-line treatment relates to its safety, efficacy, low cost, and narrow microbiologic spectrum."…”
Section: Treatment: From Managing Symptoms To Prescribing Antibioticsmentioning
confidence: 99%
“…1,2,4,6 Nearly half of all patients will improve within 1 week and two-thirds of patients will improve within 2 weeks without the use of antibiotics. 7 In children, only about 6% to 7% presenting with upper respiratory symptoms meet the criteria for acute bacterial rhinosinusitis (ABRS), 8 which we'll detail in a bit. For most patients, treatment should consist of symptom management.…”
mentioning
confidence: 99%
“…R hinosinusitis (RS) is defined as simultaneous inflammation of the nasal mucous membrane ("rhinitis") and inflammation of the mucous membrane of the paranasal sinuses ("sinusitis"), which leads to symptoms like nasal blockage, obstruction or congestion or nasal discharge (anterior, posterior, nasal drip). Additional symptoms include facial pain or pressure, the reduction or loss of smell, headache and fever (1,2).…”
Section: Introductionmentioning
confidence: 99%